Feasibility study on the application of alum sludge (AS) as alternative landfill liner material in sustainable landfill infrastructure model: XRD and SEM analysis. (November 2019) - Muhamad Bashar, N A; Syarhida Isa, N H; Sofiyah Rahman, N R; Alias, S; Chay, T C; Abdul Aziz, N H; Jamalludin, D
Abstract: The increasing number of Alum Sludge (AS) in water treatment plant (WTP) from water treatment process has been directed to the reduction of storage capacity for keeping of AS waste itself in the landfill. Other than disposed in the landfill site, this accumulated AS can be commercialized into a useful product such as landfill barrier. Conventionally, clay is used as the protection layer in the engineered sanitary landfill to reduce the leachate intrusion into groundwater. However, due to higher usage and demand on the clay (C) material caused its depletion and higher in cost. Therefore, accumulated AS can be recycled and reused to reduce the disposal problem in landfill and financial burden facing by the landfill operator. In this study, AS was investigated and compared with the kaolin clay (KC) in terms of XRD and SEM characteristics. The index properties and hydraulic conductivity, k test were also conducted to classify the AS and KC composition. Based on the testing, AS can be classified as High Plasticity Clay and the value of k for AS is higher than KC. Based on the results from XRD, both of KC and AS samples was having a similar crystalline phase which is Quartz. Based on the summary of compounds elements, the chemical elements of Oxygen, Aluminium, Silicon and Iron presence in AS have a quite similar percentage of weight (%) with KC. From all of these results, it can be concluded that the AS is mostly having similar materials to KC and amorphous in nature.